Essays in health economics - Teixeira, Adriano Dutra (2020)
The implementation of the Brazilian Programa Saúde da Família (PSF) in the 1990s was a milestone towards a primary care model based on community health workers, replacing a techno-health care model focused on hospital care. The program aims to provide basic health through professional health-care teams (composed by doctors, nurses and health agents) working at the community level. This thesis consists of three papers that seek to investigate the effects of PSF on health outcomes, using different empirical strategies of impact evaluation. As a primary care initiative with an emphasis on improving child health, the first paper assesses whether PSF has a true and lasting impact on the lives of children preventing many of them to die from avoidable causes. We conducted a quasi-experimental study following municipalities that takes into account that PSF was implemented at different times in each municipality. The data covered all the 5570 Brazilian municipalities over a two-decades period (1998-2018). Our findings highlight that program implementation do have a remarkable effect on reducing infant preventable mortality, but the effect takes a couple of years to manifest itself. As the time of exposure to PSF increases, the predicted avoidable mortality rate (per 10,000 inhabitants) reduces from 3.1 to 2.5 after 5 years of exposure, then to 1.8 after 10 years, and reaches 0.4 after 20 years into the program. The results are robust to the possibility of pre-existing trends in mortality, suggesting that there is a causal negative relationship between PSF implementation and under-five avoidable mortality. The second paper is based on the literature showing that what happens during pregnancy and youth significantly influences children\'s long-term health. The Programa Saúde da Família (PSF) has a wide range of initiatives to promote prenatal and childcare. Since the program was locally implemented in different periods of time, siblings may have been exposed to the program differently. Using Datasus and the Brazilian Household Survey, our empirical strategy aims to estimate the effect of the program\'s presence at early stages of life on children\'s health, partialling out family and regional features likely to be related to the program availability and controlling for regional specific factors that varies over time. The findings provide evidence that children exposed to the PSF early (during prenatal, at birth or during their first year of life) have better health outcomes than children not exposed to the program during their same stages of life. The program\'s effects vary across stage of life and time of exposure analyzed. The effects are heterogeneous and focused on low-income, less-educated families and vary by skin color - leading us to ponder that PSF also plays a role in reducing health inequalities. The third paper investigates whether PSF has an effect at the individual level, looking at a series of results that are closely related to primary care. Using microdata from the Pesquisa Nacional de Saúde (National Health Survey), this study estimates the effects of PSF on general health, preventive behavior and search for health. Our empirical strategy exploits a multivalued treatment effects approach by taking advantage of the information on household\'s registration in the PSF and frequency of the Family Health Teams. Our results show that the active presence of the program fosters preventive health behavior improving vaccination and preventive exams adherence, and intensifies search for public health care services, but does not have an overall effect on self-perceived health and measured indicators related to obesity and hypertension.